Development of E-Modules Based Science, Environment, Technology, and Society (SETS) on Buffer Solution Material for Class XI Senior High School - Tafani, Tafani; Widjajanti LFX, Endang (Jurnal Paedagogy, 2025)
This study aims to describe the characteristics, validity results, practicality, and student responses to SETS-based E-Modules on buffer solution material that was developed. The research uses a Research and Development (R&D) method with the 4D model, which has four stages, namely define, design, development, and disseminate. This study examined six high school chemistry teachers and 32 12th-grade students who had studied buffer solutions. The instrument used is a product quality assessment sheet, including validation sheets for material experts, media, and practitioners, as well as student responses. The data analysis technique was carried out by converting qualitative data from media experts, material experts, and chemistry teachers into quantitative data using a Likert scale and the student responses using the Guttman scale. The results showed that the SETS-based E-Module was of excellent quality and suitable for teaching on the topic of buffer solutions. This is evidenced by validation calculations performed by material and media experts, practicality tests conducted by chemistry teachers, and student responses, which yielded scores of 89%, 94%, 83%, and 80%, respectively.